Design and fabricate multifunction baby stroller - Azriq Fildza, Anuardi (2010)
This thesis shows the progress of the project entitled Design and Fabricate Multifunction Baby Stroller. The objective of this project is to design and fabricate the multifunction baby stroller according to the scoped discussed with my supervisor. The fabricating process is started after the final design is decided. Final design is chosen based on the scopes listed by me and my supervisor. The scopes is listed after thorough discussion with my supervisor based on the problem statements that happens around us, especially to the parents as they are the common users of the baby stroller to easily carry their babies or infant while travelling or just going outdoor. All this process is explained in detail in this thesis to show how the project when through the process to produce the multifunction baby stroller.